种绿萝专用有机栽培基质及其制备方法 (2018)
本发明公开了种绿萝专用有机栽培基质及其制备方法，属于无土栽培技术领域。该绿萝专用有机栽培基质是由以下重量配比的原料制成：有机腐熟基质100-150份、木屑40-60份、秸秆40-60份、豆饼30-50份、氮磷钾三元复合肥1-3份。该有机栽培基质不添加任何难以降解的矿物质原料，不会对环境造成任何影响。其原料来源丰富，成本低廉，解决了硫酸软骨素提取剩余油泥难以二次利用以及大量菠萝皮易对环境造成污染的难题，同时制备的基质保水保肥能力及透气性好，营养组分完整，完全符合绿萝的栽培生长需求，并能够大大减少或者预防病虫害的发生。 The invention discloses a special organic cultivation substrate for epipremnum aureum and a preparation method therefor and belongs to the technical field of soilless culture. The special organic cultivation substrate for the epipremnum aureum is prepared from the following raw materials in parts by weight: 100-150 parts of organic well-composted matrix, 40-60 parts of wood sawdust, 40-60 parts of straws, 30-50 parts of bean cakes and 1-3 parts of N, P and K ternary compounded fertilizer. According to the organic cultivation substrate, no mineral raw material difficult to degrade is added, so that no influence on environment can be caused. The organic cultivation substrate is rich in source of raw materials and low in cost, and the difficult problems th